The Effectiveness of Islamic-Themed Debate in Improving Speaking Fluency and Self-Efficacy Among Islamic University Students - Indrawati, Johara; Asmira, Mita (English Language and Literature in Education Journal, 2025)
The development of speaking fluency and self-efficacy remains a significant challenge for Islamic undergraduate students, particularly in contexts where English is not the primary medium of instruction. Despite extensive research on debate as a pedagogical strategy, limited studies have examined its effectiveness in an Islamic-themed context, where content is deeply rooted in religious and academic discourse. This study addresses this gap by investigating how Islamic-themed debate enhances speaking fluency and self-efficacy among Islamic university students. Employing a sequential mixed-methods approach, the research was conducted at Universitas Islam Internasional Darullughah Wadda’wah. The study involved a survey with 30 Islamic university students using a questionnaire assessing fluency (lexical resource, syntactic complexity, discourse cohesion, and speech rate) and self-efficacy (confidence, anxiety control, and perceived competence). Additionally, structured interviews with six selected participants provided deeper insights into students’ perceptions and challenges. The findings indicate that Islamic-themed debate significantly improved students’ fluency by fostering spontaneous speech production, enhancing lexical variety, and reducing hesitations. Participants also demonstrated increased confidence, reduced speaking anxiety, and a greater sense of control over their speech delivery. The integration of Islamic content into debate activities facilitated meaningful engagement, encouraging critical thinking and argumentation within an Islamic framework. These results suggest that Islamic-themed debate is an effective pedagogical approach for improving both speaking fluency and self-efficacy. The study highlights the need for curriculum designers to incorporate debate-based activities in English language programs at Islamic universities, ensuring alignment with students’ linguistic and religious backgrounds to maximize engagement and learning outcomes.